Emerging trends and future perspectives in adsorption technologies for water and wastewater treatment: A sunrise or sunset horizon? - Taher , Tarmizi; Rianjanu , Aditya (Green and Sustainable Materials Society, 2024)
Adsorption technology has been a focal point of water and wastewater treatment engineering research for over a century, yielding numerous scientific publications. These studies have primarily concentrated on developing efficient adsorbent materials, understanding adsorption mechanisms and characteristics, and investigating the removal of conventional or emerging pollutants. A common objective cited in most of these reports is the practical application of the adsorption process in municipal water or wastewater treatment plants, aiming to enhance water quality and safety. However, the majority of these studies overlook issues related to technology transfer, thereby widening the gap between academic recommendations and their practical implementation in industry. In this review, we trace the evolution of adsorption technology in water and wastewater treatment, evaluating its application viability and highlighting the approaches that hold the greatest promise for the future. Furthermore, we propose strategies for scientists and engineers dedicated to advancing research efforts that translate into industrially viable adsorption technologies for water treatment. While the practical effectiveness of adsorption technologies may not fully align with academic enthusiasm, this critical evaluation should not dismiss their potential as future technology since adsorption retains significant and distinct advantages that merit further exploration.